Designing CdS Mesoporous Networks on Co‐C@Co9S8 Double‐Shelled Nanocages as Redox‐Mediator‐Free Z‐Scheme Photocatalyst. Issue 1 (9th November 2017) - Reddy, D. Amaranatha; Park, Hanbit; Gopannagari, Madhusudana; Kim, Eun Hwa; Lee, Seunghee; Kumar, D. Praveen; Kim, Tae Kyu
Abstract: Designing porous nanostructures with unprecedented functionalities and an effective ability to harvest the maximum energy region of the solar spectrum and suppress the charge‐carrier recombination rate offers promising potential for sustainable energy production. Although several functional porous nanostructures have been developed, high‐efficiency materials are still needed. Herein, we report a new, highly active, noble‐metal‐free, and redox‐mediator‐free Z‐scheme photocatalyst, CdS/Co‐C@Co9 S8, for H2 production through water splitting under solar irradiation. The designed photocatalytic system contains open 3 D CdS mesopores as a light absorber for wider solar‐light harvesting. Metal–organicframework‐derived cobalt nanocrystal‐embedded few‐layered carbon@Co9 S8 double‐shelled nanocages were used as a co‐semiconductor to hamper the photo charge‐carrier recombination by accelerating the photogenerated electrons and holes from the other semiconductor. The optimized catalyst shows a H2 evolution rate of 26.69 mmol g −1 h −1 under simulated solar irradiation, which is 46 times higher than that of the as‐synthesized CdS mesoporous nanostructures. The apparent quantum yield reached 7.82 % at λ =425 nm in 5 h. The outstanding photocatalytic activity of CdS/Co‐C@Co9S8 reflects the favorable suppression of the charge‐carrier recombination rate, as determined by photoluminescence, photocurrent, and impedance analyses. We believe that the findings reported here may inspire the design of new noble‐metal‐free porous nanohybrids for sustainable H2 production. Abstract : That′s a good hybrid ! This work demonstrates a new design strategy for highly active, noble‐metal‐free, and redox‐mediator‐free Z‐scheme photocatalyst, CdS/Co‐C@Co9 S8, for H2 production through water splitting under solar irradiation.